Pelatihan English Listening and Speaking Application untuk Meningkatkan Kemampuan Bahasa Inggris Siswa - Idayani, Andi; Fitriah, Laila; Sailun, Betty (Jurnal Pengabdian UNDIKMA, 2024)
This service activity aims to improve the English language skills of SMK Yapim Siak Hulu students through assistance in using English listening and applications. The service's implementation method involved a training process, comprising preparation, execution, assessment, and monitoring phases. The evaluation instrument for this activity used a pre-test and post-test, which were then analyzed descriptively. This service showed that students' English language skills could improve; an increase in indicators of comprehension, vocabulary, pronunciation, and fluency proved this. Besides that, this service activity was also beneficial for students because this application helped increase students' vocabulary and speaking skills both inside and outside the classroom.